Searching for new directions for energy policy: Testing three causal models of risk perception, attitude, and behavior in nuclear energy context - Kim, Byoung Joon; Kim, Seoyong; Kim, Sunhee (International Journal of Environmental Research and Public Health, 2020)
Although many risk studies investigate perceptions, attitudes, and behaviors, the causal relationships among them have not yet been verified. Thus, further investigations of these relationships are necessary. This study analyzes three causal models consisting of three components: perceptions (i.e., perceived risk in this study), attitudes (i.e., satisfaction), and behavior (i.e., support for policy). This study checks these relationships in the context of nuclear energy policy. Using a hierarchical regression model, this study tests three different models between the three components: (1) Model 1 (a high-involvement model), (2) Model 2 (a low-involvement model), and (3) Model 3 (a hedonic model). First, in the high-involvement model, behavior is affected by perceptions and attitudes. In particular, attitudes mediate the relationship between risk perceptions and satisfaction. Second, in the low-involvement model, attitudes indirectly affect perceptions through behaviors. Third, in the hedonic model, behaviors affect attitudes, and risk perceptions do not mediate that relationship. This causal model does not depend on perceptions of the benefits and drawbacks of nuclear power. Our analysis shows that Model 1 is fully significant, and Model 2 and 3 are only partially significant.
Keywords: Attitude; Female; Humans; Male; Nuclear Energy; Public Opinion; Public Policy; Risk-Taking; Acceptance of nuclear power; Hedonic model; Nuclear energy policy; Risk perception